Penrose’s new argument and the non-locality of consciousness - Herce Fernández, Rubén (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In 1989 Roger Penrose formulated an argument against AI. This argument concludes that the scientific-mathematical explanation of reality is broader than the merely computational, because there are certain non-computational aspects of reality. This article analyzes the argument and the discussion about it, to conclude that the type of argument that Penrose wants to develop is tainted at the root, what prevents reaching the wished conclusions. At the same time the philosophical validity of his conclusions is maintained and the idea of non-locality is pointed as sound when speaking about consciousness.
Keywords: Penrose; consciousness; Gaifman; non-locality; artificial intelligence